1012 Health related quality of life of mothers of children with cancer: the role of social support and social capital - Nicolaou, Christiana; Kouta, Christiana; Papathanasoglou, Elizabeth; Middleton, Nicos (My University, 2015)
Introduction: The diagnosis of childhood cancer brings about many changes both in the lives of young patients as well as their families. It is one of the most intense, disruptive, and enduring experiences that parents can have.Aim:To investigate the Health Related Quality of Life (HRQoL) and the role of social support (SS) and social capital (SC).Methods: A cross sectional descriptive, comparative study has been performed with a purposive sample of 52 mothers of children with cancer(MCC) (study group) and 208 mothers of age- and gender-matched healthy children (MHC) (comparative group) to investigate the HRQoL and the role of SS and SC. A booklet of questionnaire was completed by both groups which contained: (a) sociodemographic characteristics and characteristics of children with cancer, (b) Medical Outcome Study (MOS) Short Form 36 Health Survey Questionnaire (SF-36), (c) Medical Outcome Study Social Support Survey (MOS−SSS-G), (d) Social Capital Questionnaire (SCQ-G).Results: The response rate of the main study group was 93% and that of the comparative group 89%. A significant difference was observed among the comparative groups on the mental dimension of HRQOL but not on the physical dimension. No significant differences were observed on their SS and SC. Although in the control group the SS and the SC showed positive relation with their physical and further more with their mental health, in MCC the protective action was restricted only in physical dimension. The main determinants of SS and SC were common in both groups (i.e. family and financial circumstances, residential status). Family was noted as the main and the most important source of support for MCC (80%), in contrast, the control group reported friends and the neighbors as important sources of support as well. However, health care providers were scored very low in both groups.
Keywords: Cancer; Children; Social support; Mothers